PERMAINAN DIKSI DAN KONDENSASI IMAJI DALAM PUISI ISLAMI KARYA TAUFIK ISMAIL (STILISTIKA SASTRA) - Nurhikma Nurhikma; Nensilianti Nensilianti; Faisal Faisal (Fakultas Bahasa dan Sastra Indoensia, 2024)
Research on Diction Games and Image Condensation in Islamic Poetry by Taufik Ismail. The research is descriptive qualitative in nature. The data source for this research is Islamic poetry by Taufik Ismail with the five best Islamic poetry titles by Taufik Imail. The title of the poem is Prophet Muhammad SAW, Prayer, Longing for the Apostle, Long Sajadah, Rasulullah Tells Us. This research data is in the form of definition, connotation, general words, specific words, abstract words, concrete words, lexical words, slang words, jargon, scientific words, loanwords, popular words. and image condensation in the form of visual images, auditive images, tactile images, and movement images. Based on Stylistics studies based on Gorys Keraf, data analysis techniques are obtained through methods of collecting data, reading data, and recording data